Azerbaijani population of Georgia in 1989-2014: demographic and linguistic aspects - Dmitry I. Uznarodov (Кавказология, 2024)
The article analyzes the demographic and linguistic aspects of the Azerbaijani issue in modern Georgia. Based on the analysis of official statistics data, the main trends in the demographic development of the Azerbaijani population of Georgia in the period from 1989 to 2014 are revealed. It is concluded that the number of Azerbaijani population in Georgia decreased by 24.23 % from 1989 to 2014, which was because of the large-scale outflow of the Azerbaijani population from Georgia during the 90s. The main linguistic aspects of the Azerbaijani issue in modern Georgia are also identified. It is concluded that, at present, among the national minorities of Georgia, the Azerbaijanis are the least integrated into the country’s linguistic space, as evidenced by the low percentage of the Azerbaijani population who are fluent in Georgian – only 18.7 %.